Oral health surveys of traditional peoples and communities in Brazil: a scope review - Maria Letícia Barbosa Raymundo; Elza Cristina Farias de Araújo; Rênnis Oliveira da Silva; Edson Hilan Gomes de Lucena; Yuri Wanderley Cavalcanti; Armando Cabral de Lira Neto; Lucas Xavier Bezerra de Menezes (BMJ Open)
Objective The objective of this review was to map the available evidence on oral health surveys of traditional peoples and communities (TPC) in Brazil, addressing the question, ‘What evidence is available on oral health surveys of traditional peoples and communities in Brazil?’.Design Scoping review according to the Scoping Review extension for the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Data sources MEDLINE/PubMed, Scopus, Web of Science, Embase and Latin American and Caribbean Literature in Health Sciences were searched up until June 2023.Eligibility criteria Studies involving individuals from indigenous groups, quilombolas, riverside communities and Romani communities, all included in TPC in Brazil, were included without any age restrictions.Data extraction and synthesis Data were extracted by two independent reviewers, and studies were categorised considering the author and year of publication, the traditional group, study type, geographical location, age group, sample size, data collection method and the main oral health condition assessed.Results After the searches, 39 studies were included in the review, and 2 studies were manually added. The studies included in the review were published between the years 1968 and 2023. Of the total, 31 studies investigated the oral health condition of indigenous peoples, 7 were studies on quilombola communities and 3 studies focused on riverside communities. No studies on Romani people were found in the search. The majority of studies were located in the Northeast region (n=12) of the country, with dental caries being the main oral health issue assessed (n=13) through clinical examinations (n=25), with a high prevalence observed among TPC (n=11).Conclusion This review reveals that in Brazil, studies on the oral health of TPC are ongoing, although they occur in an isolated and independent manner, indicating a considerably high prevalence of oral health problems in these communities.